Decreased chromobox homologue 7 expression is associated with epithelial–mesenchymal transition and poor prognosis in cervical cancer - Tian Ping (De Gruyter, 2021)
The aim of this study was to evaluate the association of the chromobox homologue 7 (CBX7) expression with the epithelial–mesenchymal transition in cervical cancer (CC), as well as with the disease prognosis. CBX7, E-cadherin (E-cad), and vimentin (VIM) expression levels were detected with immunohistochemistry. The relationship between the expression of CBX7, E-cad, and VIM expression and conventional clinicopathological characteristics of CC were evaluated. The positive expression rates of CBX7 and E-cad in the CC tissues were lower than the adjacent non-tumorous cervical tissues. Moreover, the VIM expression level was higher. The CBX7 expression was positively correlated with the E-cad expression, whereas was negatively correlated with the VIM expression. Furthermore, CBX7 was associated with the disease clinical staging, histological differentiation, lymph node metastasis, and vascular invasion. Patients with negative CBX7 expression showed decreased overall survival rates compared with those with low or high CBX7 expression. Multivariate Cox regression analysis indicated that the decreased CBX7 expression was an independent predictor for the poor prognosis of CC. In conclusion, the absence of CBX7 is associated with the histologic differentiation, lymphatic metastasis, vascular invasion, and poor prognosis of CC. CBX7 may be an independent prognostic factor for the prognosis of CC patients.